Grey eosinophils in a Miniature Schnauzer with a poorly differentiated mast cell tumor. (19th September 2019) - Irvine, Katherine L.; Raskin, Rose E.; Smith, Lauren C.; Friedrichs, Kristen R.
Abstract: A 10‐year‐old female spayed Miniature Schnauzer was presented for investigation of an intra‐nasal mass. The mass was diagnosed by histopathologic examination as an undifferentiated round cell neoplasm with an infiltrate of segmented leukocytes, interpreted as neutrophilic inflammation. The mass was treated with palliative radiation and systemic chemotherapy due to the presence of regional lymph node metastasis. During subsequent monitoring over several months, the peripheral leukocyte concentration was repeatedly within reference intervals to slightly increased with low numbers of toxic neutrophils. Four months after the initial diagnosis, there was a significant leukocytosis of 66 100 cells/μL, and 39 700 cells/μL of the leukocytes had variably mature, lobulated, and hypolobulated nuclei, and grey cytoplasm with clear vacuoles, resembling grey eosinophils. To further characterize these cells, peripheral blood smears from the patient and a canine control with eosinophilia were stained for alkaline phosphatase (AP), peroxidase, and esterase activities, and with Luxol fast blue (LFB). Histopathologic sections of the nasal mass were stained with LFB and immunohistochemically for tryptase. On blood smears, the cytoplasm of the suspected grey eosinophils stained for AP and granules stained with LFB confirmed that there was an eosinophilic lineage. Peroxidase staining was weak, and esterase staining was absent. On histopathologic sections from the nasal mass, the segmented leukocytes contained LFB‐staining granules, indicating an eosinophilic infiltrate was present. Neoplastic cells expressed tryptase, which confirms a mast cell lineage. Our findings suggest that grey eosinophils might be under‐recognized and interpreted incorrectly as toxic neutrophils. This report expands the canine breeds in which these eosinophils have been identified.